ANALISIS PENCATATAN, PENGUKURAN DAN PENGAKUAN ATAS LAPORAN PENJUALAN MENURUT PSAK 72 PADA PT. RODA ASIA HANAMI CABANG MEDAN - Cut Tasya Marshanda; Sri Fitria Jayusman; Ova Novi Irama; Ardhansyah Putra Harahap (UNIVERSITAS DHARMAWANGSA, 2026)
This study aims to analyze the recording, measurement, and recognition of revenue based on PSAK No. 72 at PT. Roda Asia Hanami, Medan Branch. The research method used is a descriptive method with a qualitative approach. Research data were obtained through interviews, observations, and documentation using primary and secondary data in the form of sales reports and company documents. Data analysis techniques were carried out by comparing the company's revenue recording, measurement, and recognition practices with the provisions of PSAK No. 72. The results of the study indicate that PT. Roda Asia Hanami, Medan Branch has not fully implemented PSAK No. 72 optimally. In the aspect of revenue recording, the company has identified contracts, determined transaction prices, and allocated transaction prices, but there are still errors in inputting transaction prices that cause inaccurate revenue recording. In terms of revenue measurement, the company measures revenue based on the price of tire retreading services according to the size and type of service, but discrepancies were still found due to errors in determining transaction prices. Meanwhile, in terms of revenue recognition, the company still recognizes revenue when a customer orders a service even though the service has not been completed and the goods have not been received by the customer. This practice is not in accordance with PSAK No. 72, which stipulates that revenue is recognized after the performance obligation is fulfilled and control over the goods or services has been transferred to the customer.